An unusual case of lumbosacral tuberculosis. (29th September 2015) - Kaur, A; Welch, S; Hackett, S; Jones, G; Solanki, G
Abstract : A 12-year-old Somalian girl was investigated for tuberculosis (TB) via contact tracing of her elder brother. She gave a 6-month history of general malaise, weight loss (documented over two clinic visits), night sweats and non-productive cough. At presentation Mantoux test (23 mm in diameter) and T spot were positive while chest radiograph and sputum culture were negative. Abdominal ultrasound scan revealed only minimal paraspinal lymphadenopathy. Positioning of the lymph nodes made biopsy confirmation difficult. In addition, she gave a 2-month history of lower back pain and possible altered sensation in her feet. Neurological examination revealed weakness on flexion of the right hip and right-sided paraesthesia of L5–S1 dermatome distribution. During her admission she complained of difficulty in micturation. Bladder ultrasound showed complete voiding. MRI scan of her lower back illustrated a large anterior paraspinal abscess with lumbosacral changes consistent with osteomyelitis. Vertebral crush fracture of L5 and S1 was also evident. In view of the abscess position and clinical findings, neurosurgical opinion was sort. It was advised she complete a 6-week programme of bed rest with use of spinal brace on mobilisation. She was commenced on quadruple anti-TB medication as well as vitamin D supplementation. She has now been discharged to home. Subsequent MRI scans have revealed a marked improvement of paraspinal abscess size and vertebral changes have remained stable. She continues to mobilise well with limited pain and the symptoms of parasethiae and difficulty in micturation have now resolved. She will receive a prolonged course of quadruple anti TB therapy, at least 9 months. This case report highlights a rare case of lumbosacral TB together with excellent images illustrating the initial lesion with marked improvement on initiation of treatment. We will discuss the evidence for and against spinal immobilisation and surgery in spinal TB in children.